2020
DOI: 10.3390/ijms21030689
|View full text |Cite
|
Sign up to set email alerts
|

Revealing and Harnessing Tumour-Associated Microglia/Macrophage Heterogeneity in Glioblastoma

Abstract: Cancer heterogeneity and progression are subject to complex interactions between neoplastic cells and their microenvironment, including the immune system. Although glioblastomas (GBMs) are classified as ‘cold tumours’ with very little lymphocyte infiltration, they can contain up to 30–40% of tumour-associated macrophages, reported to contribute to a supportive microenvironment that facilitates tumour proliferation, survival and migration. In GBM, tumour-associated macrophages comprise either resident parenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 79 publications
1
81
0
Order By: Relevance
“…It is noteworthy that in GBM the previous dual categorisation into M1proinflammatory and M2-immunosuppressive macrophage phenotype has proven to be over-simplistic and does not provide a comprehensive representation of the complex activation states observed. 28 The degree to which macrophages infiltrate the tumour has been shown to correlate with a more aggressive clinical course and reduced OS. 29 Chen et al 30 showed that macrophage-low patients (n ¼ 130) display a greater OS compared with macrophage-high IDH-wt patients (n ¼ 201).…”
Section: Tme Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that in GBM the previous dual categorisation into M1proinflammatory and M2-immunosuppressive macrophage phenotype has proven to be over-simplistic and does not provide a comprehensive representation of the complex activation states observed. 28 The degree to which macrophages infiltrate the tumour has been shown to correlate with a more aggressive clinical course and reduced OS. 29 Chen et al 30 showed that macrophage-low patients (n ¼ 130) display a greater OS compared with macrophage-high IDH-wt patients (n ¼ 201).…”
Section: Tme Characteristicsmentioning
confidence: 99%
“…33,34 Nevertheless, efforts to reprogramme TAMs may prove important for eliciting response to immune therapeutics in a subset of GBM patients. 28 In particular, mesenchymal GBM has been shown to exhibit highest TAM infiltration, 35,36 with significant macrophage content a histological signature of the subtype. Thus, notwithstanding the lack of overall clinical benefit observed to date, TAMs may yet represent a rational target in the mesenchymal setting.…”
Section: Tme Characteristicsmentioning
confidence: 99%
“…Therefore, lymphoid cells are not considered in this paper and immune cell are taken to be macrophages. It is known that GBM is relatively lymphodepleted compared to other cancers, making this approximation more feasible 27 . Full details of tumour collection, RNA-sequencing, and quality control parameters can be found in the original paper.…”
mentioning
confidence: 99%
“…While the adaptive immune system is largely absent in these mice, they retain a largely functional innate immune system, including microglia, the brain resident immune effector cells, and peripheral myeloid cells. GBM are largely lymphocyte depleted tumors 89 , while microglia and macrophages constitute the major immune component 90 . Here we show that classical glioma TME components such as microglia/macrophages, astrocytes and OPCs are present in xenografted tumors, indicating that tumor cell interactions with the TME remain active in PDOX.…”
Section: Discussionmentioning
confidence: 99%